Repositioning of Design Thinking in Science Education Research: Systematical Review - Sudarti Sudarti; Pramudya Dwi Aristya Putra; Haning Hasbiyati (Postgraduate, University of Mataram, 2023)
21st century science learning is design-based learning that can be applied with design thinking. Design Thinking in science education needs to be repositioned so that all stages can be applied to science learning. A more in-depth review of design thinking research needs to be carried out to identify research opportunities. The aim of this research is to determine the trends and focus of design thinking research, the fields of study and competencies measured by researchers in design thinking research, as well as the types of design thinking chosen by researchers. The method used in this research uses bibliometric analysis and literature review. The publications are from the last 10 years (2013-2022) from the Crossref, Google Scholar, and Scopus databases. Based on these results, it was concluded that there will be an increase in the trend of design thinking research in 2022. Eight design thinking research focuses were found with themes that are rarely researched. The field of design thinking research that is most widely applied is in the field of education, where the most researched competency is the design thinking process, but in the field of science education it is still not applied. There is a need to reposition every aspect of design thinking in science learning